Alfabetización digital en docentes de la Facultad de Ciencias de la Educación y Humanidades-UNAP, Iquitos 2022 - Malafay Navarro, Liliana Acela (2024)
The purpose of the study was to determine the level of digital literacy that teachers at the Faculty of Educational Sciences and Humanities of UNAP have. The type of research was basic with a quantitative approach and non experimental cross-sectional design. It included as a sample population 157 teachers from whom information was collected with the survey technique through a Likert-type digital literacy questionnaire. The study determined in its results that the level of digital literacy of the 157 (100.0%) teachers of the Faculty of Educational Sciences and Humanities, where 12.1% (19) of them presented a high level, the 37.6% (59) of them presented a medium level and 50.3% (79) of them presented a proportionally low level. He concluded that there is a significant challenge in improving the level of digital literacy of teachers in the Faculty of Educational Sciences and Humanities. This is because the highest percentage of teachers evidenced a low level in the management of digital systems for creating digital content, the level of communication and socialization in digital environments and information management.